DEVELOPMENT OF CHEMOTHERAPY CALCULATE DOSE PROGRAM VIA PREPRINTED ORDER TO PREVENT MEDICATION ERROR AND REDUCE TIME ORDER TO CALCULATE DOSE OF CHEMOTHERAPY - Chuentrakul, Siripa (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This research study aimed to test efficacy of chemotherapy dose-calculating tool (Chemotherapy calculate dose program via preprinted order) that resulted in reducing medication error and time to calculate dose of chemotherapy. The sample consisted of patient aged 15 years and over who get intravenous infusion of chemotherapy treatment at Panyanathaphikkhu Chonprathan Medical Center. The data before using Chemotherapy dose-calculating program was collected among 280 chemotherapy prescriptions. Comparing with the data after using chemotherapy dose-calculating program among 280 chemotherapy prescriptions. This study was to collect the data of Medication errors, Time to calculate dose of chemotherapy by physicians and Time to verify dose of chemotherapy by pharmacists. The result showed data of medication error before using the program was 5 times calculated as a rate equal to 17.85 per 1,000 chemotherapy prescriptions. Comparing with the data of medication error after using program, the medication error was 0 time calculated as a rate equal to 0 per 1,000 chemotherapy prescriptions. Chemotherapy dose-calculating program was significantly associated with 100% reduction in rate of medication error. The average times to calculate dose of chemotherapy by oncologists before using Chemotherapy dose-calculating program and after using the program were 1.34 and 0.26 minutes per one chemotherapy prescription, respectively. Chemotherapy dose-calculating program was significantly associated with 80% reduction in average time. And the average times to verify dose of chemotherapy by pharmacists before using Chemotherapy dose-calculating program and after using the program were 0.05 and 0.09 minutes per one chemotherapy prescription, respectively. Chemotherapy dose-calculating program was significantly associated with 82% reduction in average times. This research study showed chemotherapy calculate dose program via preprinted order was associated with reduction of medication error and time to calculate dose of chemotherapy. This program had benefits to patients and physicians. The limitation of program was the database cannot be online, however it can be an opportunity to develop the program in the future.